Evaluating the Role and Efficacy of Cobenfy (Xanomeline and Trospium Chloride) in Schizophrenia Treatment - review - Mazur, Michał; Żak , Katarzyna; Michalak , Katarzyna; Zukierski , Krystian; Jarych, Weronika; Pliszka , Aleksandra; Jucha , Hubert; Madyniak , Katarzyna; Kluz , Agnieszka (Quality in Sport, 2025)
Schizophrenia is a complex psychiatric disorder often resistant to dopamine-targeting antipsychotics. Cobenfy, a combination of xanomeline and trospium chloride, offers a novel approach by modulating muscarinic receptors while minimizing side effects. This review evaluates its efficacy and safety, particularly in treatment-resistant cases. Clinical trials show significant reductions in both positive and negative symptoms, positioning Cobenfy as a promising alternative.